Diabetes mellitus after renal transplantation: characteristics and risk factors - Lanerolle, R.D.; De Abrew, K.; Fernando, D.J.S.; Sheriff, M.H.R. (My University, 1995)
The prevalence of diabetes is higher among South Asians when compared to Europeans. The incidence of post-transplantation diabetes mellitus (PTDM) is 2.5% among European patients. Objective: To determine the incidence and determinants of (PTDM) in Sri Lankan patients. Design: 5 year prospective study 216 patients who had undergone renal transplantation attending the 'Renal Clinic' of the department of clinical medicine. Patients with diabetes at transplantation were excluded. Measure of outcome: 75 gram oral glucose tolerance tests were performed on all transplant patients before transplant and at 3 month intervals thereafter. Characteristics of PTDM patients were compared with a group of randomly selected 34 non-diabetic post transplant follow up control (C) patients. Results: The incidence of PTDM at one year was 15.7% (34 patients). Mean time of occurrence of PTDM was 3.1 SD 1 .4 months following transplantation. PTDM (age, 43.16 SD 9.037) were significantly older than C (age 40.33 SD 7.04) p< 0.05. Body mass index, HLA types, and total dose of steroids were similar in both groups. Total dose of cyclosporin was higher (P= 0.004) in PTDM patients (314.8 SD 313.2) than in group C (158.5 SD 177) On linear regression analysis 2 hour blood glucose correlated with BMI (r=0.4 95% C.I -0.5 to 0:71) in C and total prednisolone dose correlated with 2 hour blood glucose r = 0.36 95% .C.I 0.1 to 0.63 in PTDM. Conclusions: The incidence of PTDM in Sri Lankan renal transplant patients is higher than in Europeans.